Application of combined teaching method of case-based-learning and clinical pathway in practical gynecological teaching - Wang, Xiaoxia; Che, Xuan; Tang, Xuedong; Xu, Zhengfen (PeerJ (San Francisco, CA), 2024)
To train highly qualified medical talent in 5-year programs and improve students' analytical and problem-solving abilities, it is necessary to change the traditional teaching method. This study introduces the combined teaching method of case-based learning (CBL) and clinical pathway and evaluates its role in practical gynecological teaching. Medical students in a 5-year program who were enrolled in the fourth year were selected as the research subjects; these students were randomized into two groups that separately received either the traditional teaching method or the combined teaching method of CBL and clinical pathway. Before the internship, a questionnaire was administered to explore students' views of internship in gynecology, and after the internship, the questionnaire was administered to assess the two teaching methods. Furthermore, theoretical and skill tests were performed both before and after the internship. A total of 206 medical students in a 5-year program who were in their fourth year were enrolled in the study. Students in the experimental group performed significantly better than those in the control group. They performed significantly better in the postinternship test than in the preinternship test ( < 0.001). The questionnaire showed that more students in the experimental group thought that their learning interests, clinical skills, case analysis ability, clinical communication ability, understanding of theoretical knowledge and clinical thinking ability had improved and significantly differed between the two groups ( < 0.05). Compared to traditional teaching methods, combined teaching method of CBL and clinical pathway can elevate students' academic performance, improve their learning enthusiasm and help promote clinical teachers' teaching quality. Additionally, this novel method is effective in facilitating the achievement of teaching objectives and improving the quality of talent training. Therefore, the combined teaching method of CBL and clinical pathway should be popularized and applied in gynecological practice.